Peran Pembimbing dalam Membentuk Perilaku Istiqomah Shalat Tahajjud Santri Al-Fatih Islamic Boarding School - Wawan Juandi; Amal Amal (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
In Indonesia, Islamic Boarding Schools are a form of modernization of Islamic boarding schools, so in this millennial era, Islamic Boarding Schools are an attractive educational alternative, especia- lly for humans in this modern era. In Aceh, precisely in Bener Meriah Regency, the Al-Fatih Islamic Boarding School Foundation has been established, here researchers are interested in researching one of the routine activities of Al-Fatih Islamic Boarding School students, namely the application of ta- hajjud steadfastness in the Al-Fatih dormitory. The purpose of this study was to explore and describe the usefulness of research on the role of supervisors in shaping the behavior of istiqomah prayer ta- hajjud students of Al-Fatih Islamic Boarding School. This research method uses Bogdan and Taylor qualitative research methods that qualitative research is a procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of the study can be concluded that the role of the supervisor in the Islamic Boarding School’s Tahajjud character is: (1) being a model or role model for students in student tahajjud activities, (2) being a demonstra- tor for students, (3) as a manager for santri activities, (4) as a a guide for the life of students and the last as a motivator for the soul of students.